Reconstruction of Nasal Skin Cancer Defects with Local Flaps - A. C. Salgarelli; P. Bellini; A. Multinu; C. Magnoni; M. Francomano; F. Fantini; U. Consolo; S. Seidenari (Journal of Skin Cancer)
Reconstruction of nasal defects must preserve the integrity of complex facial functions and expressions, as well as facial symmetry and a pleasing aesthetic outcome. The reconstructive modality of choice will depend largely on the location, size, and depth of the surgical defect. Individualized therapy is the best course, and numerous flaps have been designed to provide coverage of a variety of nasal-specific defects. We describe our experience in the aesthetic reconstruction of nasal skin defects following oncological surgery. The use of different local flaps for nasal skin cancer defects is reported in 286 patients. Complications in this series were one partial flap dehiscence that healed by secondary intention, two forehead flaps, and one bilobed flap with minimal rim necrosis that resulted in an irregular scar requiring revision. Aesthetic results were deemed satisfactory by all patients and the operating surgeons. The color and texture matches were aesthetically good, and the nasal contour was distinct in all patients. All scars were inconspicuous and symmetrical. No patient had tenting or a flat nose.